Child Social and Emotional Adjustment to First Grade: The Role of Emotion-Focused Parenting - Shirley Agami-Turjeman; Roi Estlein (Behavioral Sciences, 2025)
The present study examined the associations between emotion-related parenting styles and children’s social and emotional adjustment to first grade. Hierarchical multiple regression analyses of data from 250 parents of children who had entered first grade showed that disapproving, dismissing, and laissez-faire parenting styles negatively predicted social adjustment, above and beyond other factors, such as the child’s emotion regulation and sociodemographic characteristics. Disapproving parenting also negatively predicted emotional adjustment, although this association was moderated by emotion regulation. Emotion-coaching parenting showed no significant associations with either social or emotional adjustment, indicating that scholars and professionals should pay particular attention to parenting that negates and rejects emotional aspects and is low in empathy and/or guidance. The current findings highlight the importance of considering emotional aspects of parenting for children’s adjustment to school, and they contribute to the understanding of how parental responses to children’s emotions play a role in their development and abilities to adjust during critical transition periods.